Red Cloud : a Lakota story of war and surrender - Nelson, S. D. (Abrams Books for Young Readers, 2017)
"This book is the story of the Lakota and how they were forced onto a reservation, told from the point of view of Red Cloud, warrior and chief of the Lakota. It is a heavily illustrated account, with both text and illustrations by S. D. Nelson."--Providedby publisher.